Evaluation of Dentoalveolar and Dentofacial Effects of a Mini-Screw-Anchored Pendulum Appliance in Maxillary Molar Distalization - Mümin Kırcalı; Alime Sema Yüksel (Galenos Yayinevi, 2018)
Objective:Objective:The aim of this study was to evaluate the dentoalveolar and dentofacial effects of a mini-screw-anchored pendulum appliance in maxillary molar distalization.Methods:Twenty patients with the Angle Class II molar relationship (mean age 14.05±2.4 years) were treated with a mini-screwanchored pendulum appliance for molar distalization. A mini-screw 1.9 mm in diameter and 9 mm in length was used to support the pendulum appliance. The springs of the pendulum appliance were activated at 90° and exerted 250-300 gr force per side. Lateral cephalometric radiographs and dental cast models were obtained from all the patients before and after maxillary molar distalization.Results:A 0.6° increase in the SNA and SNB angles, and a 0.3° decrease in the SN/GoGn angle were found to be statistically significant. In the maxillary first molars, 4.2-mm significant distalization, 0.6-mm significant intrusion, and 8.9° significant distal tipping were observed. The spontaneous distal drift of the maxillary second premolars was found to be statistically significant. In the maxillary first premolar and incisor positions, significant mesialization was observed; however, the changes in the angles of these teeth were found to be insignificant.Conclusion:A mini-screw-anchored pendulum appliance is an effective method for maxillary molar distalization that controls the undesired anchorage loss observed in conventional methods.